Pendampingan Media Promosi UMKM Tenun di Desa Kembang Kerang Daya sebagai Upaya Pelestarian Budaya Lokal dan Peningkatan Perekonomian Masyarakat - Farihatun Aini; Agil Arya; Laili Yuliarti; Riwaningsih; Rasid Hardi Wirasasmita; Badrul Wajdi (Politeknik Piksi Ganesha Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the weaving sector of Kembang Kerang Daya Village have strong economic and cultural potential. However, promotion and marketing are still carried out conventionally, limiting market reach. This community service program aims to improve MSME actors’ ability to use websites as digital promotional media. A descriptive qualitative method was applied through observation, interviews, and documentation. The results show that the website developed can display MSME profiles, product catalogs, and contact information, making information easier to access. The mentoring activities also improved artisans’ understanding of website management for promotion. Participants showed high enthusiasm and greater awareness of the importance of digital technology in business development. The website is expected to expand marketing opportunities, increase the competitiveness of woven products, and support the sustainable preservation of local culture and the economic growth of local weaving MSMEs.